The Role of Parents in Supporting the Development of Early Childhood Potential: A Qualitative Exploration - Azzahra, Anantha derbya; Nihwan, Nihwan; Kadir Naffati, Abdel (Universitas Islam negeri Mahmud Yunus Batusangkar, 2023)
Children are a gift given by God which is given as a mandate in carrying out tasks in the world to be useful and virtuous human beings. Parents are the first foundation for their children in teaching all education. Children's potential is a fundamental and main strength to be developed with good stimulus and directly given by parents from birth in a family environment. The importance of parents in understanding the potential development of their children in order to follow their children's interests and talents. Talent in children usually arises from hobbies they like, if parents support the development of the potential of children, these hobbies will become extraordinary talents. From the results of the author's research that at TPQ Al Amiin, the role of parents in developing the potential of early childhood is lacking because most parents there are still lacking in parenting education and several factors such as economic factors, egocentric factors and broken home factors which cause their children to become directionless.┬á